Genotypic and Phenotypic Characterization of Invasive Neonatal Escherichia coli Clinical Isolates - Shakir, Salika Mehreen; Goldbeck, Jessica Marie; Robison, Denise; Eckerd, Annette Marie; Chavez-Bueno, Susana (American Journal of Perinatology, 2014)
Objectives The objective of this study was to describe the clinical characteristics of neonates with Escherichia coli bacteremia and the antibiotic resistance pattern of the bacterial isolates. We assessed the isolates' genetic relatedness and virulence phenotypic characteristics in vitro.Study Design A total of 24 neonates with E. coli bacteremia were identified prospectively in a tertiary-care hospital. Clinical and antibiotic resistance data were investigated. The E. coli isolates were analyzed by multilocus sequence typing (MLST); the presence of the K1 capsule and their ability to invade intestinal epithelial cells were also assessed.Results Most newborns were very low birth weight infants. Overall, 75% of the isolates were ampicillin resistant and 17% were gentamicin and tobramycin nonsusceptible. MLST determined sequence types 95 and 131 (ST95 and ST131) predominated, with ST131 becoming significantly more prevalent recently. The K1 capsule was present in 50% of the isolates. ST131 isolates and those producing bacteremia in newborns younger than 7 days showed a highly invasive phenotype.Conclusion Resistance to antibiotics currently used empirically to treat newborns is present in bacteremia-producing E. coli. Clonal spread among newborns of multidrug-resistant E. coli is possible; therefore, continued surveillance is needed. Identification of additional virulence factors associated with increased invasion in neonatal E. coli strains is important and further studies are warranted.
Keywords: neonatal sepsis; Escherichia coli; antibiotic resistance; intestinal invasion